Developing Effective Customer Service Employees through Action Re-search: A Malaysian Local Authority Experience - Peter, Songan; Elizabeth, Loh; Abang Ekhsan, Abang Othman (UNIMAS Publisher, 2016)
Launching a hotline service is just one stage in the process of dealing with customers. Crucial to meeting its objectives is the development of human resources to implement the hotline. This is to ensure that quality and standard are demonstrated in order to justify its existence. This paper presents the findings and reflection of an action research intervention to improve the Hotline Complaint Service of a local authority, the Kuching City South Council in Sarawak, Malaysia. The action research process in this study involved five mini cycles of planning, acting, observing and reflecting. Visits, participant observations, interviews and questionnaires were used in the data collection process. The data were analyzed using content analysis, and the findings validated through triangulation methods. The findings suggest that there was still room for improvement in the Council’s Complaint Service. An on-the-job experience for the hotline staff was implemented during which a guideline called the “13 Basic Principles in Effective Telephone Handling”; a “Handbook” on services provided by the Public Cleansing Division; and “Form A” were created and implemented. This study shows that action research is an important component of human resource development interventions that provides employees the opportunity to acquire the knowledge and skills through on-the-job experience to improve their performance and enhance the efficiency and productivity of their organization.